2006
DOI: 10.1002/tox.20177
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin contamination of bivalves in coastal areas around northern Kyushu, Japan

Abstract: We determined tributyltin (TBT) concentrations in bivalve samples of blue mussel (Myitlus edulis), Manila clam (Ruditapes philippinarum) and pen shell (Atrina pectinata) collected from coastal areas around northern Kyushu in 1998 and 2001. TBT was detected in all bivalve samples collected, ranging in concentration from 0.008 to 0.135 microg/g wet wt. In Hakata Port, which is an industrial area, high TBT concentrations were detected in bivalves (blue mussel, maximum concentration of 0.135 microg/g wet wt). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Their study revealed that though there was a decrease in the frequency of imposex occurrence in the coasts, no significant change in the frequency of imposex was observed in harbors and bays, indicating persistence of TBT. Widespread contamination of TBT is detectable along the coastal regions of many countries (Sudaryanto et al 2002;Inoue et al 2006;Kim and Kim 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Their study revealed that though there was a decrease in the frequency of imposex occurrence in the coasts, no significant change in the frequency of imposex was observed in harbors and bays, indicating persistence of TBT. Widespread contamination of TBT is detectable along the coastal regions of many countries (Sudaryanto et al 2002;Inoue et al 2006;Kim and Kim 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The Ariake Sea is a typical semi-closed bay located in Kyushu Island, western Japan, with a maximum tidal range of 6 m in the spring tide. Inoue et al (2002) conducted on-the-spot examinations of TBT concentration in the northern Ariake Sea in 1998. In his examinations, the relatively high average TBT concentrations of 38.7 µg m −3 in the water and 4,382 µg m −3 (in unit volume of soil and water (i.e., wet weight); or 39.4 µg kg −1 in unit mass of dry soil (i.e., dry weight) at 2 cm below the bottom surface were observed at the head of the Ariake Sea, the estuary of Chikugo River, and offshore Miike Harbor.…”
Section: Study Areamentioning
confidence: 99%
“…As a result of this ban, the application of TBT in antifouling paints has become less important; however, TBT continues to adversely affect the aquatic environment, due to their use in large vessels and in countries without regulations (Fent 1996). On-the-spot examinations in semiclosed bays around Kyushu Island, Japan, revealed relatively high concentrations of TBT in coastal and harbor waters and bottom sediments (Inoue et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among marine pollutants, organotins, such as TBT, are highly toxic to a wide range of organisms (Inoue et al 2006a(Inoue et al , 2006bOhji et al 2005;Antizar-Ladislao 2008). The use of TBT in antifouling paints has been prohibited since 2008 (IMO, International Maritime Organization, www.imo.org).…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic animals, TBT is known to induce the development of male sex characteristics in females, particularly in several gastropods (Hagger et al 2006;Horiguchi 2006;Horiguchi et al 2006;Janer et al 2006;Viglino et al 2006), thus causing sterility. It also makes aquatic animals more vulnerable to infectious diseases (Anderson et al 1996) and has deleterious effects on oyster growth and reproduction (Alzieu 1991;Gagné et al 2003;Inoue et al 2004Inoue et al , 2006aInoue et al , 2006bInoue et al , 2007. Human exposure may arise from consumption of TBT-contaminated food products (Jurkeviewicz et al 2004).…”
Section: Introductionmentioning
confidence: 99%